Terahertz rectangular corrugated transmission line with Gaussian mode filtering for DNP‐NMR. Issue 13 (3rd September 2018) - Pu, Hong; Du, Chao‐Hai; Huang, Tie‐Jun; Pan, Shi; Liu, Pu‐Kun
Abstract : Gyrotrons have been developed as terahertz wave sources in dynamic nuclear polarisation (DNP) system to increase the sensitivity of nuclear magnetic resonance (NMR) in the high‐magnetic field regime. However, the transmission of the Gaussian beam from the gyrotron output window to the NMR system proves to be a critical challenge. In this study, a terahertz transmission system, composed of a rectangular corrugated waveguide and a back‐to‐back rectangular corrugated horn for Gaussian mode filtering, is proposed. The attenuation in the optimised 0.33 THz corrugated waveguide remains lower than 0.01 dB/m in a broad frequency range from 280 GHz to 450 GHz. Besides, the coupling coefficient from the electric field in the 0.33 THz mode‐filtering horn to the fundamental HE11 mode in the rectangular corrugated waveguide is obtained nearly 99.5%. This terahertz transmission system is potential to be applied in DNP‐NMR spectrometer based on continuous wave gyrotrons.